2001
DOI: 10.1002/j.2158-1592.2001.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Partner Congruence in Electronic Data Interchange (Edi)‐enabled Relationships

Abstract: Business partnerships are a prerequisite for an effective supply chain. EDI‐enabled business partnerships are crucial in linking suppliers and customers. This paper develops congruence factors for customer‐supplier EDI partnerships. Data were collected from sixty‐four customer‐supplier dyads of firms using a questionnaire instrument. By factor analyzing thirty‐one items, six congruence factors were identified: top‐level strategic commitment, trading partner flexibility, joint partnering for EDI, readiness for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 17 publications
1
45
1
Order By: Relevance
“…Commitment was not a significant driver of relationship performance for the buyer, in contrast to the work of Noordwier et al (1990), Angeles and Nath (2001), and Palmatier et al (2007). This may be due to the relative market position and size of the organizations within our study, which focuses on a dominant buyer with suppliers who were of similar or smaller size.…”
Section: Antecedents Of Relationship Performancecontrasting
confidence: 92%
“…Commitment was not a significant driver of relationship performance for the buyer, in contrast to the work of Noordwier et al (1990), Angeles and Nath (2001), and Palmatier et al (2007). This may be due to the relative market position and size of the organizations within our study, which focuses on a dominant buyer with suppliers who were of similar or smaller size.…”
Section: Antecedents Of Relationship Performancecontrasting
confidence: 92%
“…In fact, a study by Angeles and Nath (2001) found manufacturing firms to be significantly larger than supplier firms both in terms of net sales and the number of employees. Their study of buyer-supplier dyads found that nearly 52% of the buying firms employ more than 1,000 employees whereas the percentage of supplier firms employing more than 1,000 employees is only 20%.…”
Section: Sandersmentioning
confidence: 96%
“…Others have found quite the opposite while focusing specifically on performance and specific technologies rather than a technological collaboration strategy (Angeles and Nath 2001;Rogers et al 1993). Additionally, most of the supply chain and marketing technology research to date has examined one specific technology (i.e.…”
Section: Data Storage Technologiesmentioning
confidence: 99%